Right‐ventricular dysfunction in HFpEF is linked to altered cardiomyocyte Ca2+ homeostasis and myofilament sensitivity. (17th May 2021) - Hegemann, Niklas; Primessnig, Uwe; Bode, David; Wakula, Paulina; Beindorff, Nicola; Klopfleisch, Robert; Michalick, Laura; Grune, Jana; Hohendanner, Felix; Messroghli, Daniel; Pieske, Burkert; Kuebler, Wolfgang M.; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) is frequently (30%) associated with right ventricular (RV) dysfunction, which increases morbidity and mortality in these patients. Yet cellular mechanisms of RV remodelling and RV dysfunction in HFpEF are not well understood. Here, we evaluated RV cardiomyocyte function in a rat model of metabolically induced HFpEF. Methods and results: Heart failure with preserved ejection fraction‐prone animals (ZSF‐1 obese) and control rats (Wistar Kyoto) were fed a high‐caloric diet for 13 weeks. Haemodynamic characterization by echocardiography and invasive catheterization was performed at 22 and 23 weeks of age, respectively. After sacrifice, organ morphometry, RV histology, isolated RV cardiomyocyte function, and calcium (Ca 2+ ) transients were assessed. ZSF‐1 obese rats showed a HFpEF phenotype with left ventricular (LV) hypertrophy, LV diastolic dysfunction (including increased LV end‐diastolic pressures and E/e′ ratio), and preserved LV ejection fraction. ZSF‐1 obese animals developed RV dilatation (50% increased end‐diastolic area) and mildly impaired RV ejection fraction (42%) with evidence of RV hypertrophy. In isolated RV cardiomyocytes from ZSF‐1 obese rats, cell shortening amplitude was preserved, but cytosolic Ca 2+ transient amplitude was reduced. In addition, augmentation of cytosolic Ca 2+ release with increased stimulation frequency was lost in ZSF‐1 obese rats. Myofilament sensitivity was increased, while contractile kinetics were largely unaffected in intact isolated RV cardiomyocytes from ZSF‐1 obese rats. Western blot analysis revealed significantly increased phosphorylation of cardiac myosin‐binding protein C (Ser282 cMyBP‐C) but no change in phosphorylation of troponin I (Ser23, 24 TnI) in RV myocardium from ZSF‐1 obese rats. Conclusions: Right ventricular dysfunction in obese ZSF‐1 rats with HFpEF is associated with intrinsic RV cardiomyocyte remodelling including reduced cytosolic Ca 2+ amplitudes, loss of frequency‐dependent augmentation of Ca 2+ release, and increased myofilament Ca 2+ sensitivity.